The Impact of Active Labor Market Programs and Benefit Entitlement Rules on the Duration of Unemployment - Josef Zweimüller; Jan C. van Ours; Rafael Lalive (Institute for the Study of Labor (IZA), 2000)
Swiss policy makers created a unique link between unemployment benefits and Active Labor Market Programs (ALMPs) by making benefit payments conditional on program attendance after 7 months of unemployment duration. We evaluate the effect of Active Labor Market Programs and benefit entitlement on the duration of unemployment in Switzerland. In the evaluation we allow for selectivity affecting the inflow into programs. Our results indicate that (i) After ALMP-participation the transition rate to jobs increases for Swiss women but not for Swiss men. However, the job hazard rate is strongly reduced during participation. Taken together, this leads to the conclusion that programs prolong unemployment duration for men, but tend to shorten durations for women. (ii) Once the unemployment spell approaches the expiration of unconditional benefit entitlement the job-hazard rate increases strongly, both for women and for men. (iii) There are important selectivity effects for Swiss females, but not for Swiss males.
Keywords: J64; I38; C41; C14; 330; Active labor market policy; benefit entitlement; treatment effect; bivariate duration model; Arbeitsmarktpolitik; Arbeitslosigkeit; Dauer; Arbeitslosenversicherung; Wirtschaftspolitische Wirkungsanalyse; Schätzung; Schweiz